2007
DOI: 10.1590/s1516-89132007000400005
|View full text |Cite
|
Sign up to set email alerts
|

Shoot and root responses of Trifolium vesiculosum to boron fertilization in an acidic Brazilian soil

Abstract: To analyze the influence of boron fertilization on shoot and root growth of Trifolium vesiculosum (arrowleaf clover), an acid soil profile (60 cm depth with 67% Al saturation) was recreated in a column (three layers of 20 cm each). Lime and fertilizer (P and K) were incorporated into the top 20 cm. The treatments consisted of six boronrates where boric acid was mixed throughout the profile. Addition of boron to soil with low pH and high Al increased the root and shoot growth, independent of the rate applied. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
3
0
2
Order By: Relevance
“…Although some researchers have reported that B treatments can induce plant root elongation (Brdar-Jokanovic et al, 2010;Martin-Rejano et al, 2011), this was not the case here for bahiagrass, as we found no significant effects on root lengths or surface areas. Our results are consistent with those of Favaretto et al (2007) on arrowleaf clover (Trifolium vesiculosum) and Correa et al (2006) on rice (Oryza sativa).…”
Section: Bahiagrass R O O T G R O W T H a F T E R S U P P L E M E N Tsupporting
confidence: 93%
“…Although some researchers have reported that B treatments can induce plant root elongation (Brdar-Jokanovic et al, 2010;Martin-Rejano et al, 2011), this was not the case here for bahiagrass, as we found no significant effects on root lengths or surface areas. Our results are consistent with those of Favaretto et al (2007) on arrowleaf clover (Trifolium vesiculosum) and Correa et al (2006) on rice (Oryza sativa).…”
Section: Bahiagrass R O O T G R O W T H a F T E R S U P P L E M E N Tsupporting
confidence: 93%
“…Essa resposta em termos de aumento de matéria seca à adição de B também pode ser explicada pelas afirmações de Dechen e Nachtigall (2007) que relataram a atuação do B, na atividade de hormônios, e em processos biológicos como fotossíntese, metabolismo de carboidratos e do nitrogênio, influenciando à divisão celular e o acúmulo de biomassa, nos pontos de crescimento, o que poderia resultar em aumento de matéria seca da parte aérea. Respostas similares foram observadas por Favaretto et al (2007), em experimento com Trifolium vesiculosum que obtiveram um incremento de 130% na produção de matéria seca com uso de boro. Em trabalho realizado por Fageria (2000) o boro influenciou a produção de matéria seca da parte aérea e de raízes de arroz, feijão, milho, soja e trigo, sendo que as respostas variaram conforme a cultura.…”
Section: Resultsunclassified
“…Pereira et al (2008) reported similar effects of Al on sorghum root systems grown in nutrient solution. The amelioration of Al toxicity in the root system in response to B addition has been recorded in leguminous plants, particularly for root-growth related attributes (LENOBLE et al, 1996;FAVARETTO et al, 2007). Studying corn plants, Wang (2004) found no amelioration of Al rhizotoxicity with the addition of B to the nutrient solution.…”
Section: Discussionmentioning
confidence: 99%
“…The corn DM decrease with the addition of Al and the B failed to decrease this toxicity ( Figure 2). Studies have found amelioration of Al toxicity with B application generally occurs using species with a high B demand, like squash (LUBASZEWSKI; BLEVIS, 1996), clover (FAVARETTO et al, 2007), and pea (YU et al, 2009). However, in one of the few studies with grasses, Hossain et al (2004) reported amelioration of Al toxicity with the addition of B in nutrient solution for seedlings of wheat, a species with low B requirements.…”
Section: Discussionmentioning
confidence: 99%